The concept of rangeland carrying capacity in sub-Saharan Africa - myth or reality - Leeuw, P.N. de; Tothill, J.C. (Overseas Development Institute, 1993)
Up to the 1950s constraints of feed shortages for livestock were outweighed by those of disease, concern over looming imbalances between supply and demand of grazing resources led to large investments in projects of water Development, many of which were financed by foreign aid. This provision of water to hitherto under-used grazing lands further stimulated herd growth, but at the same time encouraged more settled modes of production and reduced mobility. While watering rights of man-made traditional wells were tightly enforced and served as a control on over-exploitation, water sources that were publicly financed were open to all, breaking the age-old equilibrium between water and rangeland use. The need for establishing criteria and ways for determining the carrying capacity of African rangelands become more strongly felt when in the 1960s and 1970s several regions were hit by droughts causing enormous stock losses. This chapter investigates common approaches to determine carrying capacity, elucidates the problems associated with applying the concept to improve its applicability in the continent.